Analyzing How Leadership Competencies Impact on Business Performance: A Case of Pet&Co Company - Mulyaseva, Maharani; Wisesa, Anggara (Integrasi Sains Media, 2024)
Effective leadership is crucial for aligning human capital with business objectives, thereby enhancing employee performance and organizational productivity. In the competitive pet health industry, companies like Pet&Co rely heavily on strong leadership competencies to achieve success. This study examines the impact of leadership competencies on Pet&Co's performance, focusing on issues such as unclear guidance, lack of direction, and inadequate task monitoring by the CEO. It identifies three core competencies: intrapersonal, interpersonal, and cognitive. Intrapersonal competencies, including self-awareness and self-management, are essential for personal development and effective leadership. Interpersonal skills, such as communication and empathy, are key to fostering collaboration and motivation within the team. Cognitive competencies, such as strategic thinking and decision-making, are vital for navigating complex business scenarios and driving organizational success. Utilizing qualitative methods, including interviews and observations, the study reveals that intrapersonal competencies are critical for aligning actions with organizational goals, although the CEO's low self-motivation presents a challenge. Interpersonal competencies are shown to enhance team morale and productivity, while cognitive competencies are necessary for effective strategic planning despite existing gaps in vision and innovation. The study underscores the importance of recognizing and aligning leadership competencies with strategic goals to improve business performance. Overall, the article provides valuable insights into the role of leadership competencies in enhancing organizational performance and is considered suitable for acceptance.